Prediction of Antioxidant Capacity of Thiolate-Disulfide Systems Using Species-Specific Basicity Values - Tamás Pálla; Béla Noszál; Arash Mirzahosseini (MDPI AG, 2024)
The principal reactions that maintain redox homeostasis in living systems are the deprotonation of thiols, followed by the oxidative conversion of the produced thiolates into disulfides, which thus reduce the harmful oxidizing agents. The various biological thiols have different molecule-specific propensities to carry on the co-dependent deprotonation and redox processes. This study utilizes the known correlation between thiolate basicities and oxidizabilities, to quantify antioxidant or reducing capacities and pH-dependences of thiol-disulfide antioxidant systems, as a tool to find adequate molecules against oxidative stress.